Green Perceived Value for Environmentally Friendly Products: Green Awareness Improvement - Didin Syarifuddin; Doni Purnama Alamsyah (Muhammadiyah University Press, 2017)
This study aims to review the correlation of green perceived value and green brand attribute on green awareness with supporting moderation of customer’s demographic. The review focuses on environmentally friendly products with 467 respondents who come from Supermarket’s customer in West Java Province. Hypothesis test is found that green awareness can be improved through green perceived value and green brand attribute. But green perceived value plays important role in controlling green awareness. Besides that, supporting from customer’s demographic (sex, location, income) also very influenced the correlation level of green perceived value, green brand attribute with green awareness. The study review is useful in reviewing green customer behavior particularly in Indonesia that has still poor of caring; and in the effort of facing global warming through the review on environmentally friendly products